1822 Mo. Laws 41-42 - (:unkn) unknown (My University, 1822)
An Act To Incorporate Inhabitants Of The Town Of Saint Louis, § 12: The Mayor and Board of Aldermen, shall have power by ordinance, to . . . regulate . . . the storage of gun powder, tar, pitch, rosin, hemp, cotton and other combustible materials[.]
Keywords: GUNPOWDER - STORAGE